Inducible site-directed recombination in mouse embryonic stem cells. - Zhang, Y (1996)
The site-directed recombinase Cre can be employed to delete or express genes in cell lines or animals. Clearly, the ability to control remotely the activity of this enzyme would be highly desirable. To this end we have constructed expression vectors for fusion proteins consisting of the Cre recombinase and a mutated hormone-binding domain of the murine oestrogen receptor. The latter still binds the anti-oestrogen drug tamoxifen but no longer 17 beta-oestradiol. We show here that in embryonic stem cells expressing such fusion proteins, tamoxifen can efficiently induce Cre-mediated recombination, thereby activating a stably integrated LacZ reporter gene. In the presence of either 10 microM tamoxifen or 800 nM 4-hydroxy-tamoxifen, recombination of the LacZ gene is complete within 3-4 days. By placing a tamoxifen-binding domain on both ends of the Cre protein, the enzymatic activity of Cre can be even more tightly controlled. Transgenic mice expressing such an tamoxifen-inducible Cre enzyme may thus provide a new and useful genetic tool to mutate or delete genes at specific times during development or in adult animals.